Undergraduate students’ reading preference in the extensive reading program: Diary method - Stella Prancisca; Ana Fergina; Zou Deping; Iwan Ramadhan; Muhammad Ainur Rizqi; Elsa Ananda (UPT Bahasa Universitas Tanjungpura, 2023)
Although the Extensive Reading (ER) program has multiple benefits for language learners, the long nature of this program can make it daunting, especially for those with limited book selection. Thus, ensuring a book collection that fits the learners’ preferences is crucial, not only to maintain their reading enjoyment during the program but also to save costs. This research then investigated learners' reading preferences during an ER program, particularly by looking at the reading genres that were frequently chosen by the learners. This research was conducted on 30 university students who took English as a mandatory course. The course used ER as part of the curriculum. This research recorded the learners’ reading preferences through a reading log. This log must be filled in after reading a book or text. Overall, the research generated 373 entries. The results of this research indicated participants’ high interest in books with the themes of drama (slice of life), tales, and comedy. The current research also discovered a preference difference between gender. In conclusion, this research believes ER practitioners must consider learners’ preferences to provide suitable book collections for students. Thus, the learners can read more comfortably and maintain their motivation.